Peran Ethical Governance Dalam Mewujudkan Transparansi Dan Akuntabilitas Perusahaan - Dina Nazilatul Hidayah; Dwi Sinta Amalia; Nayaka Khansa Ariella; Karina Oktaviani; Dwi Novaria Misidawati; Nanda Tribramantya Purnama (Yayasan Cendekia Gagayunan Indonesia, 2025)
The implementation of ethical governance is a crucial aspect in forming transparent and accountable corporate governance. Governance based on ethical principles is believed to be able to increase stakeholder trust and support the company's sustainability. This research aims to examine the role of ethical governance in forming transparent and accountable corporate governance. This research uses a descriptive qualitative approach with data collection techniques through literature review from various relevant sources, including the principles of Good Corporate Governance and business ethics. The results of the study show that ethical governance, which is based on the values of integrity, openness, and honesty, makes a significant contribution to increasing transparency and accountability of companies. Transparency is achieved through the delivery of accurate and timely information, while accountability is strengthened through an internal oversight system and the formation of an organizational culture that upholds ethics. In addition, the effectiveness of implementing ethical governance is influenced by internal factors such as organizational culture and management commitment, as well as external factors such as government regulations and public pressure. This study concludes that the integration of ethical principles into corporate governance is an important foundation in building transparency, accountability, and stakeholder trust, which ultimately supports corporate sustainability.